Entre sarjetas: lanceiros negros na Guerra de Farrapos (1836-1844) - Ribeiro, Vitor Gabriel Coelho (2024)
The present work aims to present the participation of enslaved people in the War of Farrapos (1835-1844), in a historical period from 1836 to 1844, when the formation of infantry groups composed of black people, called Black Lancers, occurred and who acted in favor of republican reformists against the forces of the Brazilian Empire. The objective of this work is to contribute to the construction of anti-racist education, against the erasure of the struggle for freedom of the enslaved in historical events highlighted in textbooks, in the media and in national historical memory. To analyze ethnic-racial issues and the treatment given to the Farrapos War in History Teaching, documents such as the National Common Curricular Base and the curricular parameters of the states of São Paulo and Rio Grande do Sul were used. After analyzing regulation, of federal education and the aforementioned states, imagery research was carried out, which made it possible to identify the painting Lancero de la epoch de Rivera, by Juan Manuel Blanes, as an icon for the representation of black lancers from Rio Grande do Sul, enshrined in blogs and social networks of members of black movements in Brazil. On the other hand, it was possible to confirm the erasure of black lancers in the traditional history of Rio Grande do Sul, including cultural productions, which could be verified in the comic book Guerra de Farrapos (1982). The result of the research is manifested in the form of a graphic narrative, specifically as a comic book, which presents the black lancers, their reasons for participating in the war and the characteristics that involve these individuals in the history of Rio Grande do Sul.